Direct production of high hydrogen syngas by steam gasification of Shengli lignite/chars: Significant catalytic effect of calcium and its possible active intermediate complexes. (1st September 2017) - Li, Na; Li, Yang; Zhou, Huacong; Liu, Yang; Song, Yinmin; Zhi, Keduan; He, Runxia; Yang, Keli; Liu, Quansheng
Abstract: The catalytic effect of calcium on the steam gasification of Shengli chars was studied in this work. The calcium-added chars were prepared by pyrolysis under argon atmosphere from calcium oxide added demineralized Shengli lignite. The chars were characterized in detail by SEM-EDX, XRD, Raman, FTIR and XPS and were tested on a fixed-bed reactor to evaluate its performances steam gasification. Calcium was found to have significantly promotional effect on the steam gasification of char samples with reduces of activation energy. It was observed the presences of 5  wt % or above in the char significantly enhanced H2 productions, which resulted in high H2 /CO ratio of syngas. The SEM-EDS and XRD results suggested calcium was highly dispersed within the char particles, CaO and CaS presented in the char samples, but the hydrochloric acid treatment of the char caused significant loss of these calcium compounds. The steam gasification rate of the acid-treated samples was still much higher than that of the no-calcium-added char, which elucidates that superior steam gasification performance of the Ca-added chars was not the simple CaO species in the char, instead, a special calcium lignite intermediate complex "R1 -O-Ca-O-R2 " (R representing aromatic or aliphatic constituents), formed within char during the pyrolysis. Thus the crosslink-like intermediate complexes "R1 -O-Ca-O-R2 " structure between calcium and chars was postulated to be the decisive factor to promote the steam gasification of Shengli chars with more production of high hydrogen syngas.